A 69-dB SNR 89-μW AGC for Multifrequency Signal Processing Based on Peak-Statistical Algorithm and Judgment Logic. (29th December 2016) - Dai, Lan; Chen, Chengying
Abstract : A novel peak-statistical algorithm and judgment logic (PSJ) for multifrequency signal application of Autogain Control Loop (AGC) in hearing aid SoC is proposed in this paper. Under a condition of multifrequency signal, it tracks the amplitude change and makes statistical data of them. Finally, the judgment is decided and the circuit gain is controlled precisely. The AGC circuit is implemented with 0.13 μ m 1P8M CMOS mixed-signal technology. Meanwhile, the low-power circuit topology and noise-optimizing technique are adopted to improve the signal-to-noise ratio (SNR) of our circuit. Under 1 V voltage supply, the peak SNR achieves 69.2 dB and total harmonic distortion (THD) is 65.3 dB with 89 μ W power consumption.